Do Firms sell forward for Strategic Reasons? An Application to the Wholesale Market for Natural Gas - Remco van Eijkel; Jose Luis Moraga (Tinbergen Institute, 2010)
Building on a model of the interaction of risk-averse frms that compete in forward and spot markets, we develop an empirical strategy to test whether oligopolistic frms use forward contracts for strategic motives, for risk-hedging, or for both. An increase in the number of players weakens the incentives to sell forward for risk-hedging reasons.However, if strategic motives are also relevant, then an increase in the number of players strengthens the incentives to sell forward. This difference provides the analyst with a way to identify whether strategic considerations are important at motivating frms to sell forward. Using data from the Dutch wholesale market for natural gas where we observe the number of players, spot and forward sales, and churn rates, we find evidence that strategic reasons play an important role at explaining the observed firms' (inverse) hedge ratios. In addition, the data lend support to the existence of a learning effect by wholesalers.
Keywords: D43; L13; G13; L95; 330; market power; risk-hedging; forward contracts; spot market; over-thecounter trade; market transparency; churn rates; Warenbörse; Erdgas; Marktmacht; Hedging; Risikoaversion; Spotmarkt